Evaluating Food Security Challenges during the Covid-19 Pandemic in Nigeria’s Coastal Fishing Communities - Benyin Adah Akande; Samuel A. Asua; Dennis Agiounim Undiandeye (Richtmann Publishing, 2022)
This descriptive qualitative study examined how food security was undermined during the covid-19 pandemic in some coastal fishing communities in Nigeria. The study used the Household Economic Approach as a theoretical basis to explain the challenges of food security in coastal communities based on evidence from the Covid-19 pandemic. Data were generated from open-ended interviews conducted with 30 participants in three coastal fishing communities in Akwa Ibom state, Nigeria. The study also relied on secondary data from books, reports, and journal articles. From the analysis, results showed that the various preventive measures adopted to curb the spread of the virus posed a challenge to fish production, access, and consumption. Furthermore, the findings revealed that in addition to other human security issues, covid-19 was a natural mechanism whose emergence only exacerbated existing food insecurity in coastal fishing communities. Based on the ongoing, the study concludes that, food security can be enhanced in coastal fishing communities through cross-sectorial partnerships and collaborations between the government, civil society groups and the blue economy. Received: 11 July 2022 / Accepted: 29 August 2022 / Published: 2 September 2022